Analisis Risiko Keselamatan dan Kesehatan Kerja Bagi Petugas Filing di Fasilitas Kesehatan Tingkat Lanjut - Rifa Windy Choirunnisak Rifa; Nanik Setiyawati; Anton Kristijono (Poltekkes Kemenkes Yogyakarta, 2025)
Filing room that does not pay attention to and does not apply anthropometric ergonomics aspects can pose a risk to Occupational Safety and Health. The risk factors in the filing room are direct and indirect factors. The direct factors are the area of ??the room, the distance between the storage shelves, the size of the storage shelves, temperature, humidity, noise and lighting. While the indirect factors are SOPs and work instructions for filing officers. Identification of Occupational Safety and Health policies in the form of SOPs, filing room infrastructure and K3 risk analysis in the filing room of Nur Hidayah Hospital, Bantul. This research is a qualitative research with observation, interview, documentation, and Focus Group Discussion methods and uses descriptive data analysis. The results of this study explain that Occupational Safety and Health policies in the form of guidelines, manuals, SOPs, and general work instructions already exist in written form. However, they do not yet have SOPs that regulate Occupational Safety and Health in the filing room. The availability of equipment in the filing room is incomplete, but the condition of the equipment is still suitable for use. Air temperature and humidity in the filing room have not met the ideal standard. The results of the work risk analysis in the filing room show that the highest score for the risk of work accidents is falling and slipping. The SOP for Occupational Safety and Health for the filing room does not yet exist, so hospitals need to make this SOP. The facilities and infrastructure in the filing room are incomplete. The highest work accident risk is 140 and is included in the substantial criteria.